Biathlon shooting: Previous analyses and innovative concepts - Sattlecker, G.; Buchecker, M.; Gressenbauer, C.; Müller, E.; Lindinger, S. J. (Sciene and nordic skiing III, 2016)
Biathlon is a complex winter sport combining cross country skiing and rifle shooting in several 5-shot series. The overall performance is determined by skiing time, shooting accuracy and time at the range. Despite the popularity of this sport, scientific studies in the field of biathlon shooting are rare, typically of explorative nature and rather unsystematically, mostly focusing on physiological factors (Hoffman & Street 1992; Rundell & Bacharach 1995) and the effects of body and rifle sway on score outcomes (Niinimaa & McAvoy 1983; Hoffman et al. 1992; Simoneau et al. 1997; Groslambert et al. 1998, 1999). In brief, most of the aforementioned investigations observed a strong influence of stance and rifle stability on the shooting results as well as differences in these factors between elite and novice athletes. Additionally, the physical pre-load in biathlon shooting was shown to negatively affect shooting times (Groslambert et al. 1999; Grebot et al. 2002), postural control (Hoffman et al. 1992; Simoneau et al. 1997), rifle stability (Hoffman et al. 1992) and forces in the rifle's butt plate (Grebot & Burtheret 2007). For years our research group and our training centre have been responsible for routinely screening the shooting techniques of an increasing number of national and international biathletes worldwide, both in- and off-season. Through a mufti-componental measuring station, a theory-based acquisition and analysis of a large number of expected performance determining factors was enabled. Aim of the current review is to present local methods describing shooting behaviour and to discuss corresponding published results. Furthermore, the concept of physiological-behavioral complexity in sports diagnostics will be introduced as a novel promising approach to describe basic motor control strategies. Therefore, a brief summary of associated leading theories and methodological issues is given, followed by a discussion of applied studies addressing some of the main ideas elaborated, including an overview of first data in the field of biathlon shooting mainly from the author`s lab.